Limestone and oyster shell for brown layers in their second egg production cycle - Pizzolante, CC (2011)
This study aimed at evaluating the effect of dietary calcium levels and the replacement of calcium sources with different particle size compositions on the performance and egg quality of brown layers in their second egg production cycle. A randomized block experimental design was applied with 12 treatments in a 3x4 factorial arrangement: three calcium levels (2.6, 3.2, 3.8 %) and four combinations of calcium sources (1- 100% fine limestone (FL), 2- 50% FL + 50% coarse limestone (CL), 3- 50% FL and 50% oyster shell (OS), 4- 50% FL and 25% CL+ 25 %OS), with six replicates of eight birds each. Calcium sources were analyzed for geometric mean diameter (GMD) and in-vitro solubility. The following performance and egg quality parameters were evaluated: egg weight (EW, g), egg production (% Eggs), egg mass (EM %), feed intake (FI g), feed conversion ratio (FCR kg/dz and FCR kg/kg), mortality (% Mort.), specific egg gravity (SG), percentages of yolk (Y%), albumen (Alb%) and eggshell (ES%), eggshell thickness (EST), eggshell breaking strength (BS), eggshell weight per surface area (EWSA), Haugh unit (HU), yolk index (YI) and yolk color. Performance and internal egg quality were not affected by the treatments (p>0.05). Blocks had a significant effect on (p<0.05) FI and FCR (kg/dz and kg/kg). Treatments significantly influenced external egg quality, which improved as dietary calcium levels increases and when up to 50% fine limestone was replaced by combinations of coarse limestone with oyster shell.